2002
DOI: 10.1084/jem.20010938
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Activating Interaction between Natural Killer Cells and Dendritic Cells

Abstract: We analyzed the interaction between human peripheral blood natural killer (NK) cells and monocyte-derived immature dendritic cells (DC). Fresh NK cells were activated, as indicated by the induced expression of the CD69 antigen, and their cytolytic activity was strongly augmented by contact with lipopolysaccharide (LPS)-treated mature DC, or with immature DC in the presence of the maturation stimuli LPS, Mycobacterium tuberculosis or interferon (IFN)-α. Reciprocally, fresh NK cells cultured with immature DC in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

44
876
6
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 920 publications
(931 citation statements)
references
References 23 publications
44
876
6
5
Order By: Relevance
“…On the other hand, we demonstrated that IL-12 produced by IFN-g/FMKp-matured DC also augments NK-cell cytotoxicity toward the Raji cell line. This augmentation has been documented after contact of NK cells with some bacteria or by NK-DC crosstalk during bacterial infection [11,40].In conclusion, based on our in vitro data, it can be hypothesized that in vivo a K. pneumonia infection is responsible for induction of innate immune responses characterized by DC-dependent NK-cell migration, facilitating NK-DC interactions both in the periphery and in the lymphoid tissue. The molecular program triggered by FMKp and IFN-g does not only permit DC to recruit NK cells, but also induces the prerequisites necessary to activate NK-cell cytotoxicity and NK-cell helper function for Th1 polarization and possibly subsequent CTL induction.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…On the other hand, we demonstrated that IL-12 produced by IFN-g/FMKp-matured DC also augments NK-cell cytotoxicity toward the Raji cell line. This augmentation has been documented after contact of NK cells with some bacteria or by NK-DC crosstalk during bacterial infection [11,40].In conclusion, based on our in vitro data, it can be hypothesized that in vivo a K. pneumonia infection is responsible for induction of innate immune responses characterized by DC-dependent NK-cell migration, facilitating NK-DC interactions both in the periphery and in the lymphoid tissue. The molecular program triggered by FMKp and IFN-g does not only permit DC to recruit NK cells, but also induces the prerequisites necessary to activate NK-cell cytotoxicity and NK-cell helper function for Th1 polarization and possibly subsequent CTL induction.…”
supporting
confidence: 67%
“…On the other hand, we demonstrated that IL-12 produced by IFN-g/FMKp-matured DC also augments NK-cell cytotoxicity toward the Raji cell line. This augmentation has been documented after contact of NK cells with some bacteria or by NK-DC crosstalk during bacterial infection [11,40].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…2,6,7 Specifically, NK cells have been implicated as having important reciprocal interactions with DC, facilitating collaboration between innate and adaptive immune responses. 4,5 In one carefully studied model of genetic immunization with adenovirally transduced DC that closely resembles our models, antitumor immunity was completely independent of CD8 þ T cells. 28,[40][41][42] When CD8 þ T cells were depleted using antibodies before or after immunization with AdVgp100-transduced DC, or when these DC were used to vaccinate CD8 genetically knockout mice, protection to a B16 tumor challenge was not impaired.…”
Section: Discussionmentioning
confidence: 93%
“…2 Subsequent studies have confirmed these observations in human in vitro cell cultures. [3][4][5][6][7] Additional studies focused on the possible role of NK cells in the activation of antigen-specific CTL responses generated by tumorantigen-loaded DC. Studies in both murine and human model systems showed that NK cells contributed to CTL generation.…”
mentioning
confidence: 99%